PELATIHAN E-COMMERCE BAGI WARUNG SEDEKAH (WARKAH) UNTUK MENINGKATKAN PERTUMBUHAN EKONOMI RUMAH TANGGA - Barri, Muhammad Hablul; Rizal, Achmad; Cahyadi, Willy Anugrah; Hidayat, Iswahyudi; Pramudita, Brahmantya Aji; Prihatiningrum, Novi (KACANEGARA Jurnal Pengabdian pada Masyarakat, 2021)
Warkah is a community organization that focuses on working on social activities and has many assisted residents. To develop the organization, Warkah requires additional efforts to support the organization so that it continues to be more productive. However, this corona pandemic has made an obstacle for the Warkah organization to realize the organization's vision and mission. Therefore, organizational productivity can be increased by following online sales skills. With diverse potentials and based on the socio-economic background, the ability to sell and transact online on marketplace platforms, especially on the Tokopedia, can provide material benefits. In addition, this activity also can facilitate the potential products of the GPA community members and people outside the GPA who want their products to be promoted in a broad scope. The results of the shop building training through the Tokopedia application for members of the Warkah social organization can be concluded that this training is beneficial for the Warkah organization with a high utility rating, namely 82% of participants rated this training as very useful and had high performance, namely 64% for easy understanding of the material, and 100% for the instructor's performance in delivering the material.